DISKURSUS TENTANG PERLU TIDAKNYA POLITIK HUKUM PASAR MODAL SYARIAH DI INDONESIA - Alamudi, Ichwan Ahnaz (Jurnal Ilmu Syariah dan Hukum (JISYAKU), 2024)
This study is motivated by the existence of the capital market into a reality and the latest phenomenon in the midst of the lives of Muslims in this modern century, even almost countries around the world have used the capital market as an important economic instrument to invest. In 2003, the Capital Market Supervisory Agency (Bapepam) launched the Islamic capital market. The presence of the Islamic capital market needs to be supported by stronger regulations in the form of a law. This article uses library data or library research with juridical-normative type. n this paper, the author states that the politics of law is a legal policy or official policy line regarding the law that will be enforced either in terms of making new laws or replacing old laws in the process of achieving state goals. The idea of supporting the existence of Islamic capital markets has at least four reasons behind it, namely: First, there is a belief that abundant wealth if not invested in the right place will be wasted. Second, fuqaha and Islamic economists have been able to create Islamic-based securities as an alternative to securities in circulation that are not in accordance with Islamic law. Third, it protects Muslim rulers and businessmen from speculators when investing or financing securities. Fourth, it provides a place for Islamic financial institutions and sciences related to trading techniques, while conducting sharia-compliant activities. Keywords: Political Law, Capital Market, Sharia.